Analysis of Terminal Security Issue and Solution in Mobile Internet Era - Liyun Yan; Xinzhang Yang; Gang Lu; Shaoxin Hou (Dianxin kexue)
Currently, security has been regarded as one of the greatest problems in the development of mobile Internet, the end-to-end security of mobile internet involves three dimensions: cloud security, pipe security, terminal security. The mobile intelligent terminal security, Android and iOS mobile intelligent terminal were as the representative, the security situation on mobile intelligent terminal and their solutions were discussed from the system, application, vulnerabilities and malicious code multi-angle.